Magnetic resonance imaging for congenital lung malformations - Newman, Beverley (Pediatr Radiol, 2021)
Congenital lung malformations are most often identified on prenatal US screening. Fetal MRI is often performed to further evaluate these lesions. Although some of these lesions might cause prenatal or early postnatal symptoms that require urgent management, the majority are asymptomatic at birth and might be subtle or invisible on chest radiographs. Postnatal imaging is frequently deferred until 3–6 months of age, when surgery or long-term conservative management is contemplated. High-quality imaging and interpretation is needed to assist with appropriate decision-making. Contrast-enhanced chest CT, typically with angiographic technique, has been the usual postnatal imaging choice. In this review, the author discusses and illustrates the indications and use of postnatal MR imaging for bronchopulmonary malformations as well as some differential diagnoses and the advantages and disadvantages of MR versus CT.